The impact of service marketing mix on customer satisfaction and loyalty in the casual dining industry. - Chen, Zonghao. (2009)
In this study, we aimed to examine the impact of the service marketing mix, which extends the traditional marketing mix (Product, Price, Place, and Promotion) with the service marketing mix (People, Process and Physical Evidence), on customer satisfaction and loyalty. We centered our study within the context of the casual dining restaurant industry in Singapore.